2018
DOI: 10.1038/s41371-018-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in patients with hypertension and chronic kidney disease: a randomized controlled trial

Abstract: Hypertension and chronic kidney disease (CKD) are global public health problems, both associated with higher risk of cardiovascular (CV) and renal events. This trial randomized non-diabetic adult patients with hypertension and CKD stages 2-4 to 16 weeks of aerobic and resistance training or usual care. The primary outcome was the change in estimated glomerular filtration rate (eGFR). Secondary outcomes included changes in systolic and diastolic blood pressure (BP), body weight, fasting blood glucose, lipid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 31 publications
1
57
0
1
Order By: Relevance
“…Exercise is an appealing strategy for BP control in people with CKD because exercise has shown other benefits in this population[2123] and also because the attainment of BP targets is potentially cost saving. [24] Therefore, we conducted this systematic review to evaluate the evidence for exercise as a strategy to lower blood pressure in people with non-dialysis dependent CKD (stages 3–5 estimated glomerular filtration rate <60 mL/min/1.73m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is an appealing strategy for BP control in people with CKD because exercise has shown other benefits in this population[2123] and also because the attainment of BP targets is potentially cost saving. [24] Therefore, we conducted this systematic review to evaluate the evidence for exercise as a strategy to lower blood pressure in people with non-dialysis dependent CKD (stages 3–5 estimated glomerular filtration rate <60 mL/min/1.73m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kirkman 17 42 showed different time points of measurements in the outcome data because all patients were followed for a minimum of 1.5 years or until the necessity for dialysis or kidney transplantation, which were possibilities of measurement bias. Seven trials 16,18,19,21,30,32,36 (within all reported outcomes) had enlisted in clinical trial registries or study protocols, whereas 5 trials 8,17,20,28,41 (Fig. 2).…”
Section: Percentage Of Dm (%)mentioning
confidence: 99%
“…2). Overall, 4 trials 20,29,32,42 reported the death of participants; however, those were not related to exercise training. Subgroup analysis performed for exercise types, estimated glomerular filtration rate (eGFR) (< 30 or ≥ 30 mL/min/1.73 m 2 ), and body mass index (BMI) (< 30 or ≥ 30 kg/m 2 ) showed no evidence of differences between the groups (test for subgroup difference: P = 0.74, 0.49, and 0.68, respectively).…”
Section: Percentage Of Dm (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Combined aerobic and resistance training was noted as a potential therapy in decreasing inflammation, thereby improving endothelial function in hypertensive early-stage CKD patients. [ 2 ]…”
mentioning
confidence: 99%